2018
DOI: 10.1158/2326-6066.cir-17-0218
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 33 Signaling Restrains Sporadic Colon Cancer in an Interferon-γ–Dependent Manner

Abstract: Interleukin 33 (IL33) is an inflammatory cytokine released during necrotic cell death. The epithelium and stroma of the intestine express large amounts of IL33 and its receptor St2. IL33 is therefore continuously released during homeostatic turnover of the intestinal mucosa. Although IL33 can prevent colon cancer associated with inflammatory colitis, the contribution of IL33 signaling to sporadic colon cancer remains unknown. Here, we utilized a mouse model of sporadic colon cancer to investigate the contribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 44 publications
(60 reference statements)
1
35
0
Order By: Relevance
“…Of note, another study recently reported an anti-tumoral effect of the IL-33/ST2 pathway on the development of sporadic CRC, with an increased frequency of tumor-infiltrating FOXP3 + Tregs in BM chimeric mice lacking ST2 expression on both the hematopoietic and the radio-resistant compartments. 34 These differences with our investigation may rely on the type of CRC model applied-AOM only versus AOM and DSS treatment-or the genetic background of the St2 −/− mice used-BALB/c versus C57BL/6J. Nevertheless, our data indicate that ST2 + CD4 + FOXP3 + Tregs may also promote tumorigenesis in other murine models of CRC based on genetic ablation of tumor suppressor genes critically regulating intestinal cancer.…”
Section: Discussionmentioning
confidence: 65%
“…Of note, another study recently reported an anti-tumoral effect of the IL-33/ST2 pathway on the development of sporadic CRC, with an increased frequency of tumor-infiltrating FOXP3 + Tregs in BM chimeric mice lacking ST2 expression on both the hematopoietic and the radio-resistant compartments. 34 These differences with our investigation may rely on the type of CRC model applied-AOM only versus AOM and DSS treatment-or the genetic background of the St2 −/− mice used-BALB/c versus C57BL/6J. Nevertheless, our data indicate that ST2 + CD4 + FOXP3 + Tregs may also promote tumorigenesis in other murine models of CRC based on genetic ablation of tumor suppressor genes critically regulating intestinal cancer.…”
Section: Discussionmentioning
confidence: 65%
“…Mechanistically, Twist1 can form a complex with runt‐related transcription factor 3 (Runx3) to reduce the binding of Runx3 and T‐bet to Ifng locus, which resultantly suppresses IFNγ expression . In a mouse model of sporadic colon cancer, IL‐33 treatment induces IFNγ secretion by tumor allograft‐infiltrating T cells and the deficiency of its receptor ST2 within the nonhematopoietic cells resulted in a reduced IFNγ gene expression signature . However, the mechanism underlying IL‐33‐induced IFNγ expression is needed to investigate.…”
Section: Ifnγ Expression and Significance In Cancermentioning
confidence: 99%
“…IL-33/ST2 axis seems to represent an important mediator in intestinal fibrosis. Normal epithelium and stroma of the intestine express large amounts of IL-33 and ST2 during the homeostatic turnover of the intestinal mucosa ( 39 ). It has been demonstrated that intestinal baseline IL-33 expression was present in pericryptal fibroblasts and was increased during infection ( 105 ).…”
Section: Il-33/st2 Axis In Intestinal Fibrosismentioning
confidence: 99%